Isolated parkinsonism is an atypical presentation of GRN and C9orf72 gene mutations. (November 2020) - Carneiro, Fábio; Saracino, Dario; Huin, Vincent; Clot, Fabienne; Delorme, Cécile; Méneret, Aurélie; Thobois, Stéphane; Cormier, Florence; Corvol, Jean Christophe; Lenglet, Timothée; Vidailhet, Marie; Habert, Marie-Odile; et al.
Abstract: Introduction: A phenotype of isolated parkinsonism mimicking Idiopathic Parkinson's Disease (IPD) is a rare clinical presentation of GRN and C9orf72 mutations, the major genetic causes of frontotemporal dementia (FTD). It still remains controversial if this association is fortuitous or not, and which clinical clues could reliably suggest a genetic FTD etiology in IPD patients. This study aims to describe the clinical characteristics of FTD mutation carriers presenting with IPD phenotype, provide neuropathological evidence of the mutation's causality, and specifically address their "red flags" according to current IPD criteria. Methods: Seven GRN and C9orf72 carriers with isolated parkinsonism at onset, and three patients from the literature were included in this study. To allow better delineation of their phenotype, the presence of supportive, exclusion and "red flag" features from MDS criteria were analyzed for each case. Results: Amongst the ten patients (5 GRN, 5 C9orf72 ), seven fulfilled probable IPD criteria during all the disease course, while behavioral/language or motoneuron dysfunctions occurred later in three. Disease duration was longer and dopa-responsiveness was more sustained in C9orf72 than in GRN carriers. Subtle motor features, cognitive/behavioral changes, family history of dementia/ALS were suggestive clues for a genetic diagnosis. Importantly, neuropathological examination in one patient revealed typical TDP-43-inclusions without alpha-synucleinopathy, thus demonstrating the causal link between FTD mutations, TDP-43-pathology and PD phenotype. Conclusion: We showed that, altogether, family history of early-onset dementia/ALS, the presence of cognitive/behavioral dysfunction and subtle motor characteristics are atypical features frequently present in the parkinsonian presentations of GRN and C9orf72 mutations . Highlights: Isolated parkinsonism is a presentation of GRN and C9orf72 mutations. Parkinsonism in genetic FTD may mimic the phenotype of Parkinson's Disease. FTD-related parkinsonian syndromes may occur without alpha-synucleinopathy. Family history of dementia or ALS is frequently (but not universally) present. Subtle motor features, cognitive/behavioral dysfunction are clues to the diagnosis.